Hydric characteristics and agro-industrial quality of sugarcane under application of correctives and fertilizer in Alagoas, Brazil - Silva, Ricardo Barros; Santos Neto , Antônio Lucrécio dos; Teodoro , Iêdo; Barros , Allan Cunha; Santos, Valdevan Rosendo dos; Souza , Ademária Aparecida de; Martins , Gleica Maria Correia; Santos , Wellington Manoel dos; Costa, Bruno Richardson dos Santos; Souza, José Wilker Germano de; Santos, John Kennedy dos; Silva, Dayane Mércia Ribeiro (Revista de Ciências Agroveterinárias, 2025)
The objective of this research was to evaluate meteorological variables, water balance and agro-industrial quality of sugarcane under isolated and combined application of pH correctives and organic and mineral fertilization in planting furrows, in rainfed conditions. The statistical design used was in randomized blocks, with five replications and 8 treatments: T1 = limestone, T2 = agricultural gypsum; T3 = poultry litter; T4 = T1 + T2; T5 = T1 + T3; T6 = T2 + T3; T7 = T1 + T2 + T3 and T8 = conventional mineral fertilizer. The cultivar used was RB92579 and the agro-industrial quality variables studied were: brix of broth, sugarcane broth apparent sucrose, broth purity, reducing sugars, total recoverable sugars and fiber. The air temperature was not a limiting factor for the growth of sugarcane. The crop evapotranspiration, in 16 months of cultivation, was 2,054 mm. In general, the application of agricultural gypsum in the planting furrow generates higher agro-industrial quality of the sugarcane in comparison with the application of poultry litter. The agro-industrial quality of sugarcane fields cultivated with agricultural limestone and conventional fertilization does not differ significantly from the areas where agricultural gypsum is applied or the areas where poultry litter is used.